A relação família-escola na escolarização de crianças com deficiência em Brasil Novo-PA: relatos e experiências - SILVA, Beatriz Rech da (2023)
In this work it was questioned: How does the family-school relationship influence the schooling of children with disabilities and what are their contributions to their development in teaching and learning? For this, the general objective was to reflect on the family-school relationship in the schooling of children with disabilities and its contributions to their development in teaching and learning. The research used was qualitative, carried out in Brasil Novo (BN) – Pará (PA), with self-report and as a technique the interview with semi-structured script, in which we approached four family nuclei separately. The results showed that when the family is within the child's schooling conviviality it tends to have a great evolution in the teaching-learning process, an important sense the presence of the family in the whole process of learning of the child in school. Therefore, the family-school relationship was and is fundamental because the two are bases for the educational development of people with disabilities, considering that the results showed that when the family is within the child's schooling conviviality tends to have a great evolution in the teaching and learning process. Thus, the same to follow the process of teaching learning of the student, supports the school that focuses on the particularities of each student, thus generating positive results about the school, family and social development.